Perceived parental- and peer support and relations to depressed mood and self-esteem : comparison between age groups and gender - Hrafnhildur Tinna Thorlacius 2001-; Lena Dögg Gunnarsdóttir 2001- (2023)
During the past decade, there has been a dramatic increase in mental health conditions among adolescents. The impact of social support on mental health has been examined, and it has been recognised as an important aspect of positive mental health. The aim of this study was to examine how parental and peer support related to depressed mood and self-esteem among adolescents and if those relationships differed by gender and age. The current study is a cross-sectional study that uses data from two separate surveys (one from secondary public schools and the other from upper secondary schools) from the Youth in Iceland 2018 study conducted by the Icelandic Centre for Social Research & Analysis. The sample consisted of 2,349 adolescents born between 2001 and 2003. The results indicated that both parental and peer support had positive relations to depressed mood and self-esteem in adolescents. Additionally, the findings showed that parental and peer support had more prominent relations to depressed mood and self-esteem in girls than in boys. Furthermore, in terms of the two age groups, parental support was more strongly related with depressed mood and self-esteem in the younger group. Peer support also had stronger relations to depressed mood in the younger group but had no significant relations to self-esteem across age groups. Keywords: Adolescents, Parental support, Peer support, Depressed mood, Self-esteem Undanfarinn áratug hefur orðið gífurleg aukning á geðröskunum meðal unglinga. Áhrif félagslegs stuðnings á geðheilbrigði hafa verið skoðuð og hefur félagslegur stuðningur verið viðurkenndur sem mikilvægur þáttur jákvæðrar geðheilsu. Markmið þessarar rannsóknar var að kanna hvernig stuðningur foreldra og jafningja tengist þunglyndi og sjálfsáliti ungmenna og hvort þau tengsl væru mismunandi eftir kyni og aldri. Núverandi rannsókn er þversniðsrannsókn sem notar gögn úr tveimur aðskildum könnunum (önnur framkvæmd meðal grunnskólanema en hin meðal framhaldsskólanema) úr rannsókninni Ungt fólk á Íslandi 2018 sem ...